The growing dependence of Britain on trade during the Industrial Revolution - O'Rourke, K; Clark, G; Taylor, A (University of Oxford, 2014)
Many previous studies of the role of trade during the British Industrial Revolution have found little or no role for trade in explaining British living standards or growth rates. We construct a three-region model of the world in which Britain trades with North America and the rest of the world, and calibrate the model to data from the 1760s and 1850s. We find that while trade had only a small impact on British welfare in the 1760s, it had a very large impact in the 1850s. This contrast is robust to a large range of parameter perturbations. Biased technological change and population growth were key in explaining Britain's growing dependent on trade during the Industrial Revolution.